Human Resource Management Practices and Employees’ Retention in Local Government in Uganda: A Case Study of Kisoro District Local Government. - Mugisha, Godfrey (Kabale University, 2024)
The study analyzed the relationship between human resource management practices and employee retention in Uganda's local government, specifically in Kisoro District. The study had three objectives: to examine the relationship between rewards and employee retention; to establish the relationship between training and employee retention; and to investigate the relationship between performance appraisal and employee retention. The study employed a cross-sectional research design with a mixed-methods approach and selected 325 respondents using purposive and simple random sampling techniques. The data were collected through questionnaires and interviews and analyzed using SPSS for quantitative data and content analysis for qualitative data. The findings indicated that rewards dimension has a significant positive relationship between with employee retention in Kisoro District Local Government with r=.994**, p=.000. The findings indicated that the relationship between training and employee retention was found to be statistically and positively significant since correlation coefficient of r=.905**, p=.000. Additionally, the findings showed a statistically significant positive correlation (Pearson linear correlation coefficient = .934**, p = .000) between performance appraisal and employee retention in Kisoro District Local Government. To address this issue, the researcher recommends that the district should establish enhanced rewards for staff and a salary structure that sets aside funds for employee rewards. Promotion criteria should be fair and based on staff effective performance. In addition, the researcher suggests that the district should always offer opportunities for staff training and development for improved performance and retention.